Metagenomic analysis reveals the virome profiles of Aedes albopictus in Guangzhou, China - Xu, Ye; Xu, Jiabao; Liu, Tong; Liu, Peiwen; Chen, Xiao-Guang (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Aedes albopictus is an aggressive invasive mosquito species widely distributed around the world, and it is also a known vector of arboviruses. Virus metagenomics and RNA interference (RNAi) are important in studying the biology and antiviral defense of Ae. albopictus. However, the virome and potential transmission of plant viruses by Ae. albopictus remain understudied. Methods Mosquito samples of Ae. albopictus were collected from Guangzhou, China, and small RNA sequencing was performed. Raw data were filtered, and virus-associated contigs were generated using VirusDetect. The small RNA profiles were analyzed, and maximum-likelihood phylogenetic trees were constructed. Results The small RNA sequencing of pooled Ae. albopictus revealed the presence of five known viruses, including Wenzhou sobemo-like virus 4, mosquito nodavirus, Aedes flavivirus, Hubei chryso-like virus 1, and Tobacco rattle virus RNA1. Additionally, 21 new viruses that had not been previously reported were identified. The mapping of reads and contig assembly provided insights into the viral diversity and genomic characteristics of these viruses. Field survey confirmed the detection of the identified viruses in Ae. albopictus collected from Guangzhou. Discussion The comprehensive analysis of the virus metagenomics of Ae. albopictus in this study sheds light on the diversity and prevalence of viruses in mosquito populations. The presence of known and novel viruses highlights the need for continued surveillance and investigation into their potential impact on public health. The findings also emphasize the importance of understanding the virome and potential transmission of plant viruses by Ae. albopictus. Conclusion This study provides valuable insights into the virome of Ae. albopictus and its potential role as a vector for both known and novel viruses. Further research is needed to expand the sample size, explore additional viruses, and investigate the implications for public health.